2020
DOI: 10.1002/essoar.10502420.2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Magnetic Induction Responses of Jupiter's Ocean Moons Including Effects from Adiabatic Convection

Abstract: The jovian system is of particular interest for studying magnetic induction in icy ocean worlds. Jupiter has a strong magnetic field whose dipole axis is tilted 9.6° with respect to its rotation axis (Acuna & Ness, 1976), while the orbits of the Galilean moons lie very nearly in the equatorial plane of Jupiter. This means that Jupiter's magnetic field varies in time at the orbital positions of the satellites. Also, the outer layers of the

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 39 publications
1
25
0
Order By: Relevance
“…These include the uniform icy shell thickness due to the efficient meridional heat transport of Europa’s ocean predicted in our simulations. The small meridionally variations of salinity predicted here may similarly be observable in future missions as well through its magnetic signal 49 although this may be challenging. In addition to these observable predictions, the eddy diffusivity and viscosity coefficients—estimated here from an eddy-resolving simulation of Europa’s ocean—should help in estimating ocean heat generation due to tides 41 .…”
Section: Discussionmentioning
confidence: 75%
“…These include the uniform icy shell thickness due to the efficient meridional heat transport of Europa’s ocean predicted in our simulations. The small meridionally variations of salinity predicted here may similarly be observable in future missions as well through its magnetic signal 49 although this may be challenging. In addition to these observable predictions, the eddy diffusivity and viscosity coefficients—estimated here from an eddy-resolving simulation of Europa’s ocean—should help in estimating ocean heat generation due to tides 41 .…”
Section: Discussionmentioning
confidence: 75%
“…For additional background, we refer the reader to the Supporting Information of Vance et al. (2021), where it is shown that the complex response function Akeiϕk is a special case of the complex amplitude Ane when n=1, representing the dipolar response to a uniform excitation field. Here, we negate the exponent of the complex response function, to match the definitions of past work by Zimmer et al.…”
Section: Induction Models Of Miranda Ariel and Umbrielmentioning
confidence: 99%
“…This conservative upper limit to ionospheric conductance serves as a stress test for the detection of possible oceans within the moons. For simplicity, we set a fixed height of the ionosphere as also done in previous studies (Hartkorn & Saur, 2017; Vance et al., 2021). Our modeled thickness of the ionosphere is 300 km for Ariel and Umbriel.…”
Section: Induction Models Of Miranda Ariel and Umbrielmentioning
confidence: 99%
“…Similar to the hypothesized Triton ocean, the icy Galilean moons possess subsurface oceans with conductances on the order of 104 S, sustained by thermal contributions from accretional and radiogenic sources in addition to tidal heating—except for Callisto, which receives negligible tidal heat (see, e.g., Schilling et al., 2007; Seufert et al., 2011; Saur et al., 2015; Vance et al., 2021). Each of these moons displays strong inductive responses to the changing magnetic field of their ambient magnetospheric environments (e.g., Kivelson, 2000; Saur et al., 2010) which, outside of their conducting layers, are well‐represented using a magnetic moment located at the center of each moon (e.g., Zimmer et al., 2000).…”
Section: Methodology: the Aikef Hybrid Modelmentioning
confidence: 99%